Emerging Applications and Challenges of Nanotechnology in Medicine and Nutrition - Akram, Muhammad; Mahmood, Abid; Hasan, Mohammed Khudhair; Umaru, Isaac John; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Ali, Jaouher Ben (Darul Yasin Al Sys, 2025)
Emerging applications of nanotechnology in medicine and nutrition present both significant opportunities and challenges that warrant thorough investigation. This study aims to explore the intersection of nanotechnology and genomic nutrition, focusing on how these advancements can enhance preventive care and health outcomes. Employing a qualitative descriptive methodology, we conducted a comparative analysis of existing literature and case studies to assess the implications of these technologies on dietary customization and patient-provider relationships. Our findings reveal that nanotechnology facilitates the development of targeted nutritional interventions that align with individual genetic profiles, thereby improving adherence to dietary guidelines and mitigating disease risk. Furthermore, we identify that the integration of continuous health monitoring technologies fosters a collaborative partnership between patients and healthcare providers, enhancing communication and decision-making processes in treatment and preventive initiatives. The implications of this research underscore the necessity for healthcare systems to adopt technological advancements to address the complexities of modern medicine effectively. By embracing these innovations, the potential for precision medicine is significantly amplified, paving the way for improved health outcomes and personalized nutrition strategies in the future.